2020
DOI: 10.5858/arpa.2020-0232-sa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Severe Acute Respiratory Syndrome Coronavirus 2 Infection on Pregnant Women and Their Infants

Abstract: Context: The pandemic of a novel coronavirus, termed SARS-CoV-2, has created an unprecedented global health burden. Objective: To investigate the effect of the SARS-CoV-2 infection on maternal, fetal, and neonatal morbidity and other poor obstetrical outcomes. Design: All suspected cases of pregnant women with Coronavirus Disease 2019 (COVID-19) admitted into one center of Wuhan from Jan 20, 2020 to March 19, 2020 were included. Detailed clinical data of those pregnancies with COVID-19 were retrospectively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 20 publications
0
16
0
20
Order By: Relevance
“…Neonatal death was reported in 5 (2.0%) of 251 COVID-19 pregnancies (3 due to prematurity and 2 due to sepsis), and only one (0.4%) of 251 live-born newborns was RT-PCR positive after birth [10]. In the study conducted by Zhu et al, one of the babies of nine COVID-19 positive mothers died, while five were hospitalized in the neonatal intensive care unit [25]. In their study, Yang et al reported neonatal death in only 1.2% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal death was reported in 5 (2.0%) of 251 COVID-19 pregnancies (3 due to prematurity and 2 due to sepsis), and only one (0.4%) of 251 live-born newborns was RT-PCR positive after birth [10]. In the study conducted by Zhu et al, one of the babies of nine COVID-19 positive mothers died, while five were hospitalized in the neonatal intensive care unit [25]. In their study, Yang et al reported neonatal death in only 1.2% [11].…”
Section: Discussionmentioning
confidence: 99%
“…With reference to the laboratory findings, in our study, 15.7% of the pregnant patients had lymphopenia, and elevated ALT and AST were observed in 24.2% and 11.2% of the patients, respectively, and 10% had elevated D-dimer. Several studies have reported lymphopenia in both the general population affected by COVID-19 [36] and also in pregnant women affected by COVID-19 [17, 37]. Similarly, a retrospective study found the likelihood of lymphopenia as well as increased concentrations of ALT or AST as one of the clinical manifestations [13].…”
Section: Discussionmentioning
confidence: 99%
“…disease with the majority of cases occurring in the late second and third trimesters. 10,31,[44][45][46]49,60,[84][85][86][87][88][89][90] Little data are available on the effects of infection occurring in the first or early second trimesters.…”
Section: Maternal Mortalitymentioning
confidence: 99%